The use efficiency of textile machines and equipment - Borkowski, Stanisław; Krynke, Marek (Univerzita Pardubice, 2014)
In this paper, an analysis of the efficiency of machines used in the textile industry. The test results are based on the selected coefficients TPM, enabling comprehensive assessment the degree of working time use of these machines.